The lability of organic groups in the reaction of 2-(2-pyridyl)phenyl(p-ethoxyphenyl)tellurium(II) with palladium (II) and platinum (II) chlorides - Mbogo, S. A. (Tanzania Journal of Science, 2021)
Reaction between 2- (- pyridyl )phenyl(p-ethoxyphenyl)tellurium(II), RR'Te, and PdCl2 or PtCl2 are complex. The organic groups R and R' are labile, trans-metallation to form RM-groups (M=Pd, Pt) occurs. The solid phases isolated have well defined stoichiometries, eg R'TePdCl, R2R'TePtCl5 and these are discussed together with IR, 1H and 195Pt NMR data.